A Bilingual Advantage for Episodic Memory in Older Adults - Schroeder, Scott R. (2012)
The ability to remember events – referred to as episodic memory – is typically subject to decline in older adulthood. Episodic memory decline has been attributed in part to less successful executive functioning, which may hinder an older adult’s ability to implement controlled encoding and retrieval processes. Since bilingual older adults often show more successful executive functioning than monolinguals, they may be better able to maintain episodic memory. To examine this hypothesis, we compared bilingual and monolingual older adults on a picture scene recall task (assessing episodic memory) and a Simon task (assessing executive functioning). Bilinguals exhibited better episodic memory than their monolingual peers, recalling significantly more items overall. Within the bilingual group, earlier second language acquisition and more years speaking two languages were associated with better recall. Bilinguals also demonstrated higher executive functioning, and there was evidence that level of executive functioning was related to memory performance. Results indicate that extensive practice controlling two languages may benefit episodic memory in older adults.